2011
DOI: 10.1080/10803548.2011.11076902
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence: A Study of Turkish Workers

Abstract: This research was conducted to address the experience of workplace violence of Turkish workers from different sectors and to investigate the impact of the exposed violence on their psychological well-being. Data were collected anonymously with printed questionnaires from the volunteer participants and depended on self-reporting. The response rate was 79.0% (1708/2161). The prevalence of workplace violence was found to be 44.8%. The most common type was verbal violence together with mobbing (bullying). Victims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
5
22
2
3
Order By: Relevance
“…The findings of bullying research conducted in many parts of the world in recent years clearly demonstrate the serious dimensions of workplace bullying (Aytac et al, 2011;Tinaz, 2012;Tonini et al, 2011aTonini et al, , 2011b and how violence in the health care sector is more common than in other workplaces (Annagür, 2010). It has been reported that health care professionals, and nurses in particular, are more commonly bullied than those in other professions (Gallant-Roman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of bullying research conducted in many parts of the world in recent years clearly demonstrate the serious dimensions of workplace bullying (Aytac et al, 2011;Tinaz, 2012;Tonini et al, 2011aTonini et al, , 2011b and how violence in the health care sector is more common than in other workplaces (Annagür, 2010). It has been reported that health care professionals, and nurses in particular, are more commonly bullied than those in other professions (Gallant-Roman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many other cross-sectional studies have focused on the consequences of violence on HCWs. Assaults are associated with high job strain [34], burnout [35], anxiety [36], depression [37, 38], post-traumatic stress disorder [39, 40], and reduced productivity [41]. WV is associated with high psychological distress, low superior and coworker support, and low interactional justice [42].…”
Section: Discussionmentioning
confidence: 99%
“…Research on other professionals has come to similar conclusions, indicating that this kind of bullying is more common in male managerial roles (2). In Turkey, a questionnaire dispensed to a large working population found that, in many and varied employment areas, men are at increased risk of physical aggression, while women are more exposed to verbal, psychological and sexual abuse (16). According to our data, Bjorkqvist et al reported that, among mobbing victims (within the university), about 2/3 are women (17).…”
Section: Discussionmentioning
confidence: 86%